A story of resilience: Arctic diatom Chaetoceros gelidus exhibited high physiological plasticity to changing CO2 and light levels - Biswas, Haimanti (Frontiers in Plant Science, 2022)
Arctic phytoplankton are experiencing multifaceted stresses due to climate warming, ocean acidification, retreating sea ice, and associated changes in light availability, and that may have large ecological consequences. Multiple stressor studies on Arctic phytoplankton, particularly on the bloom-forming species, may help understand their fitness in response to future climate change, however, such studies are scarce. In the present study, a laboratory experiment was conducted on the bloom-forming Arctic diatom Chaetoceros gelidus (earlier C. socialis) under variable CO2 (240 and 900 µatm) and light (50 and 100 µmol photons m-2 s-1) levels. The growth response was documented using the pre-acclimatized culture at 2° C in a closed batch system over 12 days until the dissolved inorganic nitrogen was depleted. Particulate organic carbon and nitrogen (POC and PON), pigments, cell density, and the maximum quantum yield of photosystem II (Fv/Fm) were measured on day 4 (D4), 6 (D6), 10 (D10), and 12 (D12). The overall growth response suggested that C. gelidus maintained a steady-state carboxylation rate with subsequent conversion to macromolecules as reflected in the per-cell POC contents under variable CO2 and light levels. A substantial amount of POC buildup at the low CO2 level (comparable to the high CO2 treatment) indicated the possibility of existing carbon dioxide concentration mechanisms (CCMs) that needs further investigation. Pigment signatures revealed a high level of adaptability to variable irradiance in this species without any major CO2 effect. PON contents per cell increased initially but decreased irrespective of CO2 levels when nitrogen was limited (D6¬ onward) possibly to recycle intracellular nitrogen resources resulting in enhanced C: N ratios. On D12 the decreased dissolved organic nitrogen levels could be attributed to consumption under nitrogen starvation. Such physiological plasticity could make C. gelidus “ecologically resilient” in the future Arctic.